Correction: Luminescent Nd2S3 thin films: a new chemical vapour deposition route towards rare-earth sulphides. Issue 44 (31st October 2019) - Cwik, Stefan; Beer, Sebastian M. J.; Schmidt, Marcel; Gerhardt, Nils C.; de los Arcos, Teresa; Rogalla, Detlef; Weßing, Jana; Giner, Ignacio; Hofmann, Martin; Grundmeier, Guido; Wieck, Andreas D.; Devi, Anjana
Abstract : Correction for 'Luminescent Nd2 S3 thin films: a new chemical vapour deposition route towards rare-earth sulphides' by Stefan Cwik et al., Dalton Trans., 2019, 48, 2926–2938.